(untitled) - Barker, A. J. (New York, 1973)
Yamashita surrendered on 3rd September 1945; on 25th September he was charged with being a war criminal. In November a military tribunal set up in by General MacArthur convicted him of having failed to provide effective control over his troops and for this crime, hitherto unknown in the annals of jurisprudence, Yamashita was sentenced to death. An appeal to the U.S. Supreme Court was rejected and then president Truman refused to take action on petition for clemency, Yamashita's fate was certain.
Keywords: Generals,Yamashita, tomobumi; Biography; 1885-1946; Japan